Accountability for Management of Village Fund Allocations in Klari Village, Karawang Regency for 2020 – 2021 - Rachman, Dimas Alwi; Purnamasari, Hanny; Gumilar, Gun Gun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to examine the level of accountability in managing village fund allocations in Klari Village. Allocation of village funds is an important source of funding aimed at encouraging the development and welfare of the community at the village level. However, to achieve this goal, it is important for the village to have good accountability in managing these funds. This research uses a qualitative approach by conducting in- depth interviews with various related parties, such as the village head, village officials, community leaders, and villagers. The collected data were analyzed using a descriptive method to describe the current state of accountability. The results of the study show that accountability in managing village fund allocations in Klari Village still needs to be improved. Several factors affect the level of accountability, namely the lack of transparency in village financial reporting, the low level of community participation in making decisions regarding the allocation of funds, and the lack of outside supervision. In addition, there are administrative and technical obstacles that impede the efficient use of village funds. The use of information technology that has not been maximized is also one of the challenges in increasing accountability. Therefore, the recommendations from this study are the importance of increasing transparency, community participation, and external oversight in managing village fund allocations. In addition, a better understanding of related regulations and the use of information technology is needed to increase efficiency and effectiveness in managing village funds.